S01-1: Active Lives, Diverse Places: Co-Production of the Movement Inspired by Martial Arts Programme to Support Physical Activity and Healthy Ageing in Diverse Communities (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The project aimed to co-produce a novel, multicomponent intervention to support sustainable physical activity among older adults in ethnically diverse communities. Promoting physical activity in this population is vital for maintaining independence, improving quality of life, and reducing dementia risk. However, physical inactivity remains a significant public health concern. Co-production approaches can help develop effective, sustainable interventions, particularly in socially disadvantaged communities.Project Description: The Movement Inspired by Martial Arts (MIMA) programme was developed in Cardiff through three stages: (1) Engaging diverse middle-aged and older adults to identify key factors for sustaining and increasing physical activity, including barriers and facilitators to exercise. (2) Designing a hybrid martial arts programme focused on coordination, learning, and social interaction. (3) Gathering participant feedback through evaluation forms and focus groups at MIMA showcase events in three highly deprived, ethnically diverse areas. Overall, 72 participants took part in stages 1 and 3, with 12 actively involved in co-production. Stakeholders from the Wales Martial Arts Research Network, public health, local council, and third sector supported recruitment, and eight representatives joined the co-production process.The final programme includes non-contact martial arts movements targeting coordination and strength, along with educational materials, group sessions, and structured social interaction to promote adherence. Participants appreciated the co-production process, and showcase events demonstrated strong interest and enjoyment across diverse groups. Stakeholders reported benefits related to social interaction, flexibility, and reduced fall risk.The MIMA pilot is implemented from May 2025 and evaluated using qualitative methods and field-based measures. Volunteer MIMA ambassadors are being trained to help sustain and expand the programme and support its wider dissemination.Conclusions: Integrating co-production with stakeholder engagement offered several benefits, including increased uptake and greater likelihood of the programme being perceived as feasible by older adults, supporting recruitment. Reporting on MIMA’s development process may benefit researchers designing interventions for older adults. Future research is focused on upscaling and evaluating the programme. Recommendations for promoting health-enhancing physical activity in diverse communities: (1) Build trust through compassionate public engagement activities and collaborative work with communities. (2) Establish a stakeholder network from early stages of development to support implementation.Funding/Support Source: The co-production stage of the project received funding from the Wales Innovation Network in 2024 and the implementation of MIMA pilot is funded by the National Lottery Awards for All.Keywords: Co-production, martial arts, ethnically diverse, community-based